Військово-історичні пам’ятки у збірках музеїв Львова першої половини XX ст. - Петрик, Н. Р. (Publishing House of Lviv Polytechnic National University, 2014)
Досліджено нагромадження військово-історичних пам’яток у львівських музейних колекціях кінця XIX – першої половини XX ст., а також процес створення спеціалізованих військово-історичних музеїв. Розкрито внесок у музейне будівництво громадських та культурних інституцій та окремих діячів. An accumulation of military and historical attractions in a museum collections of Lviv from the end of XIX until the first half of the XX century and a process of creating military and historical museums has been investigated in this article. A contribution of the public and cultural institutions and any public and scientific figures in the museum construction has been revealed. The national factor was one of the most important in a public life of Lviv at that time. Polish and Ukrainian communities strived to create their own independent states. Their desires were represented in a museum construction. The main figure in this process was Alexander Cholovscy. National Museum of King Jan III was the top museum institution of Polish community in Lviv. This Museum had one of the largest collection of military historical attractions. Besides, there were large military and historical collections from a Museum of the Princes Lubomyrski and Boleslaw Ozhehovych collection. All these museum institutions and collections belongs to the Polish cultural society. The main museum of Ukrainian community was the Museum of Shevchenko Scientific Society. Collection of the military and historical attractions of this Museum began to take shape at the end of XIX century. Subsequently military and historical attractions were united into a single department. And in 1937 the Museum of military and historical attractions of Shevchenko Scientific Society or Museum Liberation Straggle was created from this department. It was the first historical museum of Ukrainian community in Lviv, which specialized on military. During the World War II collections of Lviv museums had suffered losses. A large part of the military and historical collections were destroyed; another one was moved abroad. Lviv museums were reorganized. That’s why, in 1940 all military and historical attractions, that were saved, have been focused in the new Lviv Historical Museum. Nowadays collections of Lviv museums from the first half of the XX century are the most important sources for learning the military history in Western Ukraine.